1923 Cal. Stat. 696, § 3 - (:unkn) unknown (My University, 1923)
Prohibited committing a felony while armed with weapons named in §1 or while armed with any pistol, revolver, or other firearm capable of being concealed upon the person, without having a license to carry. Violators shall be punishable by felony, with imprisonment in a state prison for not less than five nor more than ten years.
Keywords: CARRY - INTENT TO COMMIT CRIME